Properties and function of the medial patellofemoral ligament: A systematic review - Huber,C; Zhang,Q; Taylor,WR; Amis,AA; Smith,C; Hosseini,Nasab SH (American Journal of Sports Medicine, 2020)
BACKGROUND: As the main passive structure preventing patellar lateral subluxation, accurate knowledge of the anatomy, material properties, and functional behavior of the medial patellofemoral ligament (MPFL) is critical for improving its reconstruction. PURPOSE: To provide a state-of-the-art understanding of the properties and function of the MPFL by undertaking a systematic review and statistical analysis of the literature. STUDY DESIGN: Systematic review. METHODS: On June 26, 2018, data for this systematic review were obtained by searching PubMed and Scopus. Articles containing numerical information regarding the anatomy, mechanical properties, and/or functional behavior of the MPFL that met the inclusion criteria were reviewed, recorded, and statistically evaluated. RESULTS: A total of 55 articles met the inclusion criteria for this review. The MPFL presented as a fanlike structure spanning from the medial femoral epicondyle to the medial border of the patella. The reported data indicated ultimate failure loads from 72 N to 208 N, ultimate failure elongation from 8.4 mm to 26 mm, and stiffness values from 8.0 N/mm to 42.5 N/mm. In both cadaveric and in vivo studies, the average elongation pattern demonstrated close to isometric behavior of the ligament in the first 50° to 60° of knee flexion, followed by progressive shortening into deep flexion. Kinematic data suggested clear lateralization of the patella in the MPFL-deficient knee during early knee flexion under simulated muscle forces. CONCLUSION: A lack of knowledge regarding the morphology and attachment sites of the MPFL remains. The reported mechanical properties also lack consistency, thus requiring further investigations. However, the results regarding patellar tracking confirm that the lack of an MPFL leads to lateralization of the patella, followed by delayed engagement of the trochlear groove, plausibly leading to an increased risk of patellar dislocations. The observed isometric behavior up to